A one health approach to plant health - Vivian Hoffmann; Birthe Paul; Titilayo Falade; Arshnee Moodley; Navin Ramankutty; Janice Olawoye; Rousseau Djouaka; Elikana Lekei; Nicoline de Haan; Peter Ballantyne; Jeff Waage (CABI Agriculture and Bioscience)
Abstract One Health has been defined as an approach to the pursuit of public health and well-being that recognizes the interconnections between people, animals, plants, and their shared environment. In this opinion piece, based on a webinar of the same name, we argue that a One Health perspective can help optimize net benefits from plant protection, realizing food security and nutrition gains while minimizing unintentional negative impacts of plant health practices on people, animals and ecosystems. We focus on two primary trade-offs that lie at the interface of plant health with animal, ecosystem, and human health: protecting plant health through use of agrochemicals versus minimizing risks to human health and antimicrobial and insecticide resistance; and ensuring food security by prioritizing the health of crops to maximize agricultural production versus protecting environmental systems critical for human health. We discuss challenges and opportunities for advancement associated with each of these, taking into account how the priorities and constraints of stakeholders may vary by gender, and argue that building the capacity of regulatory bodies in low- and middle-income countries to conduct cost–benefit analysis has the potential to improve decision-making in the context of these and other multi-dimensional trade-offs.